Impacto dos exercícios hipopressivos na reabilitação do assoalho pélvico de mulheres com prolapso genital: estudo prospectivo, randomizado e controlado - Resende, Ana Paula Magalhães [UNIFESP] (2010)
Aim: To evaluate the effects of hypopressive exercises associated with pelvic floor muscles voluntary contraction in pereineal muscles of women with pelvic organ prolapse. Methods: In randomized controlled trial were compared two groups: intervention group (GI) and control group (GC). The groups were evaluated regarding to pelvic floor muscle function and pelvic organ prolapse stage. To evaluate the function, were used bidigital palpation, trough Oxford scale and the muscular endurance, time of contraction maintain in seconds. The surface electromyography was also used. It evaluates the pelvic floor muscle electrical activity. The pelvic organ prolapse stage was classified according to the Pelvic Organ Prolapse Quantification (POP-Q), by a gynecologist. The patients of GI Group underwent three individual sessions for learning the exercises, followed by three months of home exercises, with monthly appointments and fortnightly phone calls. The GC Group underwent to only one session, when received orientation to perform home exercises, without following a defined protocol. Both groups were revaluated after three months. Results: Were included 21 patients in GI group and 16 patients in GC group. The GI Group presented improvement of muscle function, measured by Oxford (p < 0,001), endurance (p < 0,001) and maximum voluntary contraction (MVC), evaluated trough surface electromyography (p=0,001). When compared both groups, GI group presented superior muscle function. With regard to pelvic organ prolapse, 70% of women in GI group decreased on stage of prolapse. This fact occurs in only 21% of women in GC group. Conclusion: hypopressive exercises associated with voluntary pelvic floor muscle contraction improved muscle function and decreased pelvic organ prolapse.